Reflection on the Moderating Role of Islamic Work Ethics and Psychological Capital on the Impact of Abusive Supervision on Deviant Behaviors among Semnan Public organizations Employees - Morteza Maleki Minbashrazgah (Imam Hussein University, 2020)
Workplace deviance is one of the undesirable behaviors which are responded by employees due to abusive supervision in the workplace. Abusive supervision is one of the crucial topics in the knowledge of the body of management literature. The employees display aggression and retaliation behavior against supervisor interpersonal mistreatment, and ultimately employees engage with deviant behavior. Psychological capital and Islamic work ethic reduces the effect of workplace deviance in the presence of abusive supervision. The purpose of this study was to investigate the Moderating Role of Islamic Work Ethics and Psychological Capital on the Impact of Abusive Supervision on Deviant Behaviors. The present study was conducted with the purpose of applied and descriptive-correlation method. The statistical population of the study was all employees of public organizations in Semnan province. Samples were selected through simple random sampling, which 218 people was determined according to the size of society in each organization. Tepper (2000) standard questionnaire was used to measure abusive supervision variables, The standard questionnaire of Bennett and Robinson (2000) was used to measure deviant behavior, Islamic work ethics was obtained from the Tufail et al (2017) standard questionnaire and psychological capital from the standard Luthans et al (2015) questionnaire. Questionnaires were analyzed using structural equations’ modeling in Smart-PLS software. The results showed that Abusive supervision has a positive and significant effect on employee's deviant behavior. Also, Islamic Work Ethic and psychological capital moderates the relationship between abusive supervision and employees deviant behaviors.